2019
DOI: 10.2147/idr.s201849
|View full text |Cite
|
Sign up to set email alerts
|

<p>Changing antibiotic susceptibility pattern in uropathogenic <em>Escherichia coli</em> over a period of 5 years in a tertiary care center</p>

Abstract: Objective: To assess the changing antibiotic sensitivity pattern in Uropathogenic E. coli over a period of time (2013–2017) with a special emphasis on ESBL-producing E. coli. Methods: This retrospective study was carried out in the Department of Microbiology, Kasturba Medical College, Ambedkar Circle, Mangalore. A retrospective time bound analysis of 500 samples/year was performed. The urine samples received from the suspected cases of uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 8 publications
3
33
1
1
Order By: Relevance
“…Patwardhan et al had earlier reported a significant increase in AMR in North India over a period of five years [ 26 ]. In a study from another part of South India by Prasada et al over five years on E. coli infections, there was a significant increase in resistance for quinolones and piperacillin-tazobactam [ 27 ]. The study also showed a significant increase in the prevalence of ESBL producers over the study period (45% in 2013 to 60% in 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Patwardhan et al had earlier reported a significant increase in AMR in North India over a period of five years [ 26 ]. In a study from another part of South India by Prasada et al over five years on E. coli infections, there was a significant increase in resistance for quinolones and piperacillin-tazobactam [ 27 ]. The study also showed a significant increase in the prevalence of ESBL producers over the study period (45% in 2013 to 60% in 2017).…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 In recent years, antibiotic-resistant E. coli in urinary tract infections is increasing, predominantly ESBL-EC. 21 Therefore, we need to be highly vigilant for serious bloodstream infections caused by urinary tract infection bacteria entering the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…In England, the nonsusceptibility to third-generation cephalosporins for UPEC from hospital specimens from 6.3% in 2010 to 7.4% in 2013. 7 In Canadian, multidrugresistant (MDR) phenotypes of UPEC from outpatients increased from 9.7% in 2007 to 16.5% in 2016. 8 We present AMR data from routine laboratory-based surveillance of UPEC isolates in Southwest China for the period 2012-2019.…”
Section: Introductionmentioning
confidence: 99%